Analysis of the Level of Satisfaction of Prabumulih University Students on the Use of the Tiktok Social Media Application Using the Usability Testing Method - Elpeni Damayanti; Andi Christian; Muchlis (Yayasan Kita Menulis, 2024)
In the digital era that we are experiencing, there are many developments that occur every year, including in the field of digital technology. With the rapid development of information technology, new discoveries have been made that have an impact on today's society. The convenience provided by the internet has succeeded in changing people's lifestyles today. In fact, nowadays the use of the internet is no longer limited to a communication medium but has become a promotional medium, information medium, entertainment medium and much more. One of the entertainment media applications that people are currently interested in is the TikTok application. An information system is said to be successful if the information is processed to produce good information, but user satisfaction and acceptance of the system or application is also one measure of the success of the information system. This research aims to determine the level of satisfaction of users of the Tiktok application. This research uses quantitative methods and content variables, accuracy, ease of use and timeliness. The sampling technique uses a purposive sampling method. Process analysis uses the usability method with five variables, namely learning ability, efficiency, memory, errors and satisfaction.